PERAN KYAI DALAM MENDIDIK KARAKTER SANTRI MELALUI BUDAYA PESANTREN SALAF DI PONDOK PESANTREN TARBIYATUN NASYIIN PACULGOWANG JOMBANG - Rahman, Abd.; Masruroh, Laily; Ilahiyah, Iva Inayatul (EL-Islam, 2024)
The Tarbiyatunnasyiin Islamic boarding school is one of the Salaf Islamic boarding schools that really pays attention to the personality traits of its students. Character formation is built by bringing to life the cultural values of Salaf (traditional) Islamicboarding schools. For example, by teaching the basics of faith which are learned through Salaf books such as the books Kifayatul 'Awam and Aqidatul 'Awam, habitual worship activities which can be obtained through congregational prayers, reciting the Koran and murojaah, as well as upholding morals. The focus of this research is 1) How is the Character Education of Santri at the Tarbiyatunnasyiin Pacul Gowang Jombang Islamic Boarding School? 2) What is the Salaf Islamic Boarding School Culture like at theTarbiyatunnasyiin Pacul Gowang Jombang Islamic Boarding School? 3) What is the role of Kyai in shaping the character of students through Salaf Islamic boarding school culture at the Tarbiyatunnasyiin Pacul Gowang Jombang Islamic boarding school? The research in this thesis uses a qualitative approach method. The type of research used in this research is case study research. Data collection techniques are observation, interviews, documentation and triangulation. The results of the research are as follows: 1) The character education of students at the Tarbiyatunnasyiin Islamic boarding school is formed, one of the ways, by the presence of figures or role models and also formed by the existence of rules or regulations. 2) The Salaf culture at the Tarbiyatunnasyiin Islamic boarding school has two sides, namely first from the side of life or activity conditions which are still very traditional which are farfrom luxurious and modern, and second from the learning method or system which still uses and even emphasizes the Salaf method, namely sorogan., bandongan, memorization and deliberation. 3) The role of kyai in educating the character of students through Salaf culture at the Tarbiyatunnasyiin Islamic boarding school cannot be separated from the existence of role models, namely the elders of the Islamic boarding school. The elders used to shape the character of their students not only by teaching knowledge from certain books, but also by providing guidance and becoming role models for their students.